2018
DOI: 10.1007/s40519-018-0538-6
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcome of males treated for anorexia nervosa: a review of the literature

Abstract: Level I, Systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Remission rates after 6 years in our study were nearly identical in males and females treated for AN (40% vs. 41%). Most published studies on the outcome of AN included very small sample sizes of males (7–14 males), studies with higher sample sizes reported mortality only (Strobel et al, ). Length of follow‐up and definition of remission varied between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remission rates after 6 years in our study were nearly identical in males and females treated for AN (40% vs. 41%). Most published studies on the outcome of AN included very small sample sizes of males (7–14 males), studies with higher sample sizes reported mortality only (Strobel et al, ). Length of follow‐up and definition of remission varied between studies.…”
Section: Discussionmentioning
confidence: 99%
“…This should result in distinct differences in outcome between males and females. There are few longitudinal comparisons between treated males and females: A review (Strobel, Quadflieg, Voderholzer, Naab, & Fichter, ) on males with AN found widely varying outcomes after treatment with no clear evidence of gender differences. In addition to the sparse number of reports and small sample sizes, the outcome definitions varied, and males and females were often not adequately matched (Strobel et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies addressing mortality exclusively in males. A recent review of selected outcome studies on anorexia nervosa (AN) in males (Strobel, Quadflieg, Voderholzer, Naab, & Fichter, ) reported a total number of 22 deceased out of 553 males included in 21 studies, which allows a rough estimate of overall crude mortality of 4.0% in a heterogeneous group of males. Three deaths (3.1%) occurred in 96 males at less than 5 years follow‐up, and 19 of 457 male participants (4.2%) died after more than 9 years.…”
Section: Introductionmentioning
confidence: 99%
“…• The small clinical samples and their heterogeneity [6]. • In the general population studies, instruments and designs are really different and poorly comparable [7].…”
mentioning
confidence: 99%